2020
DOI: 10.5812/jjm.104089
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Fungi on the IL-1β Expression in Mouse Dendritic Cells

Abstract: Background: Invasive fungal infection received more and more attention because of its high mortality, Candida albicans and Aspergillus fumigatus is the most common pathogenic fungus for systematic fungal infection, A. lentulus was isolated and identified recently and named as a sister of A. fumigatus. Objectives: The current study aimed to explore the concentration and time-dependent relationships of the virulence of fungi due to the change in the Interleukin-1 beta (IL-1β) level. Methods: Candida albicans, A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…These results are due to the IL-1β activation upon the presence of C. albicans . Similar results were observed by Zhang et al [ 87 ] in their study of the effects of different fungi on IL-1β expression in mouse dendritic cells. They observed that C. albicans had a significant inflammation-inducing effect in a concentration and time-dependent pattern.…”
Section: Resultssupporting
confidence: 91%
“…These results are due to the IL-1β activation upon the presence of C. albicans . Similar results were observed by Zhang et al [ 87 ] in their study of the effects of different fungi on IL-1β expression in mouse dendritic cells. They observed that C. albicans had a significant inflammation-inducing effect in a concentration and time-dependent pattern.…”
Section: Resultssupporting
confidence: 91%